Implementasi Wisata Edukasi Di Agrowisata Doesoen Kakao Kecamatan Glenmore, Kabupaten Banyuwangi - Wahyu Prana Yoga; Dian Pramita Sugiarti; I Made Bayu Ariwangsa (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
Banyuwangi is one of the famous regency in East Java province because rapid tourism development. Banyuwangi has a many tourism potential like view of the stretch of mountains, beaches, forests and local culture. Tourism in Banyuwangi has various types, one of the most enjoyed is educational tourism especially at Agrotourism Doesoen Kakao Glenmore. This study aims to analyze the implementation of educational tourism in Agrotourism Doesoen Kakao is feasible or not. This research used qualitative methods with quantitative and qualitative data. Sampling determine technique using purposive sampling for informants. The data collection techniques used are, interviews, observations, library studies and documentation. The result of this research is that educational tours Agrotourism Doesoen Kakao almost have met all the criteria. There are three criteria, namely Naturalness, Contribution to Society, and Conducting Development. Agrotourism Doesoen Kakao still does not conduct development in several parts. Agrowisata Doesoen Kakao needs to make more attractions and provide services that add more comfort to tourists. Keyword: Education Tourism, Agrotourism, and Tourism